2004
DOI: 10.1002/cjoc.20040220710
|View full text |Cite
|
Sign up to set email alerts
|

Chemical liquid phase deposition of thin aluminum oxide films

Abstract: FilmsSUN, Jie "'(bJ\@) SUN, Thin aluminum oxide films were deposited by a new and simple physicochemical method called chemical liquid phase deposition (CLD) on semiconductor materials. Aluminum sulfate with crystallized water and sodium bicarbonate were used as precursors for film growth, and the control of the system's pH value played an important role in this experiment. The growth rate is 12 nm/h with the deposition at [A12(SO&]=O.O837 mol-L-', [NaHC03]= 0.214 mol-L-', 15 %. Post-growth annealing not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The spectra have no C-related peaks after CVD, implying atomic-scale thickness. The curves before and after graphene growth are very similar (no additional features in 3000-3700 cm −1 range), 19,20 suggesting the lack of −OH groups. This offers an advantage over the wet-transferred graphene, where H 2 O is likely to be trapped at the interfaces.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The spectra have no C-related peaks after CVD, implying atomic-scale thickness. The curves before and after graphene growth are very similar (no additional features in 3000-3700 cm −1 range), 19,20 suggesting the lack of −OH groups. This offers an advantage over the wet-transferred graphene, where H 2 O is likely to be trapped at the interfaces.…”
mentioning
confidence: 89%
“…15 A similar example can be found in liquid phase deposition, where flat substrates help sol particles to form thin films as opposed to the otherwise favorable clumpy precipitates. 19,20 The discussion above can be generalized to explain graphene growth on any nonmetallic substrate that withstands ∼1000 o C by CVD using hydrocarbons, not limited to CH 4 . Obviously, the substrate materials and their preparation play an important role in the growth kinetics.…”
mentioning
confidence: 99%
“…1 This lower temperature deposition also does not influence device characteristics and wiring reliability because of decreased thermal stress, and thus it is useful on multilevel interconnection interlayer dielectrics. [5][6][7] During LPD, oxides are precipitated and form thin films such as titanium oxide (TiO 2 8 and strontium titanate (SrTiO 3 . 9 Silicon dioxide (SiO 2 ) thin films also may form during LPD, and these films are quite versatile and applicable to various fields.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al reported that the growth speed of aluminum oxide thin films, which are deposited by chemical liquid phase deposition on semiconductors, are influenced by experimental conditions such as reagent concentration and reaction temperature. 5 They also investigated the growth mechanism of aluminum oxide thin films and propose a model for the pH-controlled deposition of Al 2 O 3 . Tsukuma et al reported that the formation of SiO 2 films, including the film composition and properties, is influenced by silicic acids with organic functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…An attractive candidate for outstanding Si surface passivation is aluminum oxide (Al2O3), which can be deposited by physical vapor deposition (PVD) system [ 1], chemical vapor deposition (CVD) system [2-4], liquid-phase deposition (LPD) technique [5,6], and atomic layer deposition (ALD) system [7][8][9]. Generally, ALD system is the most suitable choice for the deposition of Al2O3 owing to some advantages: (i) capable of producing very thin conformal and uniform films, (ii) with large process temperature window, and (iii) able to deposit films on high-aspect-ratio substrates.…”
Section: Introductionmentioning
confidence: 99%